Schaum’s outline of theory and problems of differential and integral calculus - Ayres, Frank (McGraw-Hill, 1990)
This is a great book for anyone who wants to learn or supplement his or her knowledge of the subject. I have used this book for my first year of college calculus and thanks to it I received an A, because of that I will continue to use it, it helps you understand the problems, but you actually have to think about them, you have to find out how equations are related and/or used, that is calculus, Calculus involves thinking if it didn't then anyone could be a physicist.